An investigation into the effectiveness of relative and absolute atmospheric correction for retrieval the TSM concentration in inland waters - Bernardo, Nariane [UNESP]; Watanabe, Fernanda [UNESP]; Rodrigues, Thanan [UNESP]; Alcantara, Enner [UNESP] (Springer, 2016)
The absolute atmospheric correction inputs are not always available, and then such parameters are assumed based on geographical location, acquisition time and sensor type. These assumptions can imply in errors in retrieving the remote-sensing reflectance (R-rs), and affects the optically active compounds estimates. As an alternative, relative atmospheric correction, i.e. radiometric normalization, can be used in cases where there is no information about atmospheric conditions. The main goal of this work was to perform a comparative analysis between absolute and relative atmospheric correction to estimate total suspended matter (TSM) concentrations in the Barra Bonita Hydroelectric Reservoir (Sao Paulo State, Brazil). The corrections were applied to the operational land imager, on-board Lansat-8 satellite. The Rrs errors from each correction were computed considering in situ data, and the lowest error was obtained for green spectral band (RMSEabsolute = 11.5 % and RMSErelative = 12.3 %). Using a regional algorithm that was developed using the in situ measurements (the model was TSM = 1742.7*B3 - 5.42, with R-2 = 0.60, p-value = 0.05), the estimated TSM concentrations from absolute and relative corrections retrieved a RSME of 11 and 6 %, respectively. The errors from absolute correction can be originated from the input parameters that were adopted, such as CO2 concentration, initial visibility, and water vapor information. The relative correction can be more appropriate in such cases because, besides atmospheric effects, the method try to minimize the illumination variability using normalization between temporal images, which improves the reflectances, and consequently, decreases TSM retrieval errors.
Keywords: Inland water; IRMAD; FLAASH; Retrieval errors; Reservoir; Case-2 water